1974
DOI: 10.1149/1.2396838
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Studies of Uranium and Thorium in Molten LiF-NaF-KF at 500°C

Abstract: Electrochemical studies of U(IV) in molten normalLiF‐normalNaF‐KF (46.5‐11.5‐42.0 mole per cent) at 500°C reveal a two‐step reduction process at a platinum electrode. The first step is complicated by disproportionation of U(III) to regenerate U(IV); the second step involves formation of uranium metal. Standard electrode potentials with respect to a unit mole fraction Ni(II)/Ni electrode are estimated for the U(IV)/U(III) and U(III)/U couples as −1.41 and −1.81V, respectively. These values must be considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 13 publications
7
22
0
Order By: Relevance
“…The anodic peak corresponding to stripping of deposited thorium metal was detected during the back scan after the peak belonging to oxidation of alkali metal reduced during the melt decomposition. The measured voltammograms qualitatively well agreed to the data published by Clayton et al (1974) and the typical one is also at Fig. 3.…”
Section: Electrochemical Characteristics Of Uranium and Thorium Speciessupporting
confidence: 88%
See 1 more Smart Citation
“…The anodic peak corresponding to stripping of deposited thorium metal was detected during the back scan after the peak belonging to oxidation of alkali metal reduced during the melt decomposition. The measured voltammograms qualitatively well agreed to the data published by Clayton et al (1974) and the typical one is also at Fig. 3.…”
Section: Electrochemical Characteristics Of Uranium and Thorium Speciessupporting
confidence: 88%
“…Its electrochemical behaviour was found to be similar in each melt, when a twostep reduction up to uranium metal was observed. Both reactions seem to be quite well reversible and in case of FLINAK, measured voltammograms correspond well to theoretical assumptions and they are also in very good agreement with data published by Clayton et al (1974) [4]. In case of LiFCaF 2 melt, the ratio between maximums of current densities of the peaks does not correspond to the expected value 1:3, albeit the potential difference between the peaks is almost the same in both melts.…”
Section: Electrochemical Characteristics Of Uranium and Thorium Speciessupporting
confidence: 88%
“…Clayton and Mamantov [8] studied uranium electrochemical behaviour in the same bath at 500 • C. They also observed U(0) and U(III) oxidation. As the previous author, they attributed it to a reaction of U metal with potassium: U + K(I) = U(IV) + 4K.…”
Section: Study Of the Second Step Of The Reduction Process: Reductionmentioning
confidence: 96%
“…Several authors have already reported U metal instability in LiF-NaF-KF melts (46.5-11.5-42.0 mol%) [8,31]. Young [31] worked at 525 • C and studied uranium by spectrophotometry.…”
Section: Study Of the Second Step Of The Reduction Process: Reductionmentioning
confidence: 99%
See 1 more Smart Citation